Minimizing residual occult nodal metastasis in NSCLC: recent advances, current status and controversies. Issue 2 (1st February 2020) - Dezube, Aaron R; Jaklitsch, Michael T
ABSTRACT: Introduction : Nodal involvement in lung cancer is a significant determinant of prognosis and treatment management. New evidence exists regarding the management of occult lymph node metastasis and residual disease in the fields of imaging, mediastinal staging, and operative management. Areas covered : This review summarizes the latest body of knowledge on the identification and management of occult lymph node metastasis in NSCLC. We focus on tumor-specific characteristics; imaging modalities; invasive mediastinal staging; and operative management including, technique, degree of resection, and lymph node examination. Expert opinion : Newly identified risk-factors associated with nodal metastasis including tumor histology, location, radiologic features, and metabolic activity are not included in professional societal guidelines due to the heterogeneity of their reporting and uncertainty on how to adopt them into practice. Imaging as a sole diagnostic method is limited. We recommend confirmation with invasive mediastinal staging. EBUS-FNA is the best initial method, but adoption has not been uniform. The diagnostic algorithm is less certain for re-staging of mediastinal nodes after neoadjuvant therapy. Mediastinal node sampling during lobectomy remains the gold-standard, but evidence supports the use of minimally invasive techniques. More study is warranted regarding sublobar resection. No consensus exists regarding lymph node examination, but new evidence supports reexamination of current quality metrics.